2006
DOI: 10.2214/ajr.05.0407
|View full text |Cite
|
Sign up to set email alerts
|

IV Contrast Administration for CT: A Survey of Practices for the Screening and Prevention of Contrast Nephropathy

Abstract: A wide variation of practice patterns is apparent in the screening and prevention of contrast nephropathy. In some cases, these patterns conflict with recommendations from the literature. The results of this study identify opportunities for further research and areas in need of improved practice guidelines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0
3

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(47 citation statements)
references
References 36 publications
0
44
0
3
Order By: Relevance
“…commonly used to assess nephrogenic systemic fibrosis risk before examinations enhanced with gadolinium-based contrast agents (11,24). We showed that IV LOCM is nephrotoxic in patients with stable pre-CT eGFR of less than 30 mL/min/1.73 m 2 , with a trend toward significance in patients with stable pre-CT eGFR of 30-44 mL/min/1.73 m 2 .…”
Section: Multivariate Analysismentioning
confidence: 74%
See 3 more Smart Citations
“…commonly used to assess nephrogenic systemic fibrosis risk before examinations enhanced with gadolinium-based contrast agents (11,24). We showed that IV LOCM is nephrotoxic in patients with stable pre-CT eGFR of less than 30 mL/min/1.73 m 2 , with a trend toward significance in patients with stable pre-CT eGFR of 30-44 mL/min/1.73 m 2 .…”
Section: Multivariate Analysismentioning
confidence: 74%
“…In recent years, retrospective studies have shown similar rates of post-CT acute kidney injury (AKI) in nonenhanced and contrast-enhanced CT populations (2,(5)(6)(7)(8)(9)(10), which led some to question the incidence of CIN in this setting and whether it occurs at all (3,4). This topic has considerable clinical relevance because concern for renal toxicity is a main reason to avoid IV contrast material in some patients (11)(12)(13)(14)(15). Nonuse of IV contrast material leads to impaired diagnostic ability in many situations, while liberal use of IV contrast material may result in renal compromise.…”
Section: Subjectsmentioning
confidence: 99%
See 2 more Smart Citations
“…The ESUR guideline is supported by a large propensity-matched retrospective multivariate analysis of adult inpatients with stable renal function (20) that showed that IV iodinated contrast medium is a borderline nephrotoxic risk factor in patients with an eGFR of 30-44 mL/min/1.73 m 2 and is a substantial nephrotoxic risk factor in patients with an eGFR of lower than 30 mL/min/1.73 m 2 . The ESUR position is also supported by findings in other series (21)(22)(23)(24) that demonstrated that the incidence of post-computed tomographic (CT) acute kidney injury is highly correlated with increasing stage of chronic kidney disease, with those patients who have an eGFR of lower than 45 clinical landscape (3). In a 2006 survey of academic, private, and mixed radiology practices in the United States, Elicker et al (3) demonstrated that 92% (369 of 400) of all surveyed radiologists still used an SCr level-based threshold value to stratify CIN risk prior to inpatient examinations, while only 2% (eight of 400) used estimated creatinine clearance.…”
Section: Contrast Media: Contrast Medium-induced Nephrotoxicity Risk mentioning
confidence: 55%